2016
DOI: 10.1126/science.aac9475
|View full text |Cite
|
Sign up to set email alerts
|

Broadly targeted CD8 + T cell responses restricted by major histocompatibility complex E

Abstract: Major histocompatibility complex (MHC)-E is a highly conserved, ubiquitously expressed, non-classical MHC-Ib molecule with limited polymorphism primarily involved in NK cell regulation. We found that vaccination of rhesus macaques (RM) with ΔRh157.5/.4 Rhesus Cytomegalovirus (RhCMV) vectors results in MHC-E-restricted presentation of highly varied peptide epitopes to CD8α/β+ T cells, approximately 4 distinct epitopes per 100 amino acids in all tested antigens. Computational structural analysis revealed that MH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
434
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 273 publications
(452 citation statements)
references
References 56 publications
18
434
0
Order By: Relevance
“…The role of MHC-E in both NK cell regulation and antigen presentation to CD8+ T cells is conserved in mice (29–34), but few studies have investigated MHC-E function in physiologically relevant NHP models. Recently, we described the induction of pathogen-specific MHC-E-restricted CD8+ T cell responses in rhesus macaques (RM, Macaca mulatta) after vaccination with rhesus cytomegalovirus (RhCMV)-based vaccine vectors (35), confirming the role of Mamu-E in antigen presentation to CD8+ T cells. RhCMV-based vaccination with SIV antigens (RhCMV/SIV) elicits SIV-specific, Mamu-E-restricted CD8+ T cells and results in robust control and clearance of SIV infection in approximately fifty percent of vaccinated rhesus macaques (36), suggesting pathogen-targeted MHC-E-restricted CD8+ T cells might serve as effective anti-viral immune responses.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…The role of MHC-E in both NK cell regulation and antigen presentation to CD8+ T cells is conserved in mice (29–34), but few studies have investigated MHC-E function in physiologically relevant NHP models. Recently, we described the induction of pathogen-specific MHC-E-restricted CD8+ T cell responses in rhesus macaques (RM, Macaca mulatta) after vaccination with rhesus cytomegalovirus (RhCMV)-based vaccine vectors (35), confirming the role of Mamu-E in antigen presentation to CD8+ T cells. RhCMV-based vaccination with SIV antigens (RhCMV/SIV) elicits SIV-specific, Mamu-E-restricted CD8+ T cells and results in robust control and clearance of SIV infection in approximately fifty percent of vaccinated rhesus macaques (36), suggesting pathogen-targeted MHC-E-restricted CD8+ T cells might serve as effective anti-viral immune responses.…”
Section: Introductionmentioning
confidence: 78%
“…The creation of single chain trimer constructs (SCTs) has been previously described in detail (35, 53). Briefly, each construct encodes a fusion protein of MHC-E signal peptide, peptide of interest, human β2M, the mature form of MHC-E of interest or Mamu-A1*001:01 (α1 through cytoplasmic domain), and EGFP connected by flexible linker regions ([GGGGS] X ).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, a direct correlation between Gag-specific T cell responses prior to infection and control of acute viremia was found in DNA-vaccinated macaques (32). Others found that the inclusion of Gag in the vaccine was critical for the control of viremia using recombinant vesicular stomatitis virus (33,34), and recombinant human CMV (35,36) vaccines. We identified seven CE that represent 54% of the HIV-1 p24 Gag protein, and are found in nearly every HIV-1 (M group) strain observed to date throughout the world (19,(23)(24)(25).…”
mentioning
confidence: 99%
“…On the other hand, Hansen et al 90 , 91 reported no protection from virus acquisition but found robust control of viremia in ∼half of the rCMV (SIV Gag) immunized macaques. A fundamental difference between our and the rCMV vaccine is that DNA vaccination induces T cell immunity using canonical MHC molecules, while certain rCMV vectors are able to elicit T cell immunity through the non-canonical MHC-E, 94 , 95 a feature that makes the rCMV vector induced responses unique. In a study designed to mimick elite controllers, Mudd et al 69 reported that vaccination of Mamu B*08 + macaques with recombinant yellow fever 17D (rYF17D)/rAd5 vectors expressing three Mamu B*08 restricted Nef and Vif CD8 epitopes resulted in efficient control of viremia.…”
Section: Discussionmentioning
confidence: 99%